Combining midfacial degloving, LeFort-I osteotomy and inferiorly extended lateral orbitotomy (Krönlein) for removal of an orbital cavernous haemangioma: a new approach. Issue 10 (October 2018) - Schwaiger, M.; Wallner, J.; Zemann, W.; Feichtinger, M.
Abstract: Orbital tumours, located in the medial extraconal and intraconal compartment of the orbit, represent a challenge, with regard to surgical exposure. In the present paper removal of a cavernous haemangioma, located in the medial intraconal compartment was accomplished by combining lateral orbitotomy, midfacial degloving and LeFort-I osteotomy. Resection of the tumour could be performed under direct vision. Surgical exposure and removal of the lesion were obtained, without causing damage to surrounding tissues. Aesthetical results and postoperative eye function proved to be highly satisfactorily. With regard to limitations, concerning the combination of these methods, extended surgery duration and invasiveness have to be named. According to the technical feasibility and postoperative results, this new surgical approach represents a reliable and fully viable alternative method for the removal of medial orbital tumours.